Literature Review: Pengaruh Relaksasi Otot Progresif terhadap Kualitas Tidur pada Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis: Literature Review: The Effect of Progressive Muscle Relaxation on Sleep Quality in Chronic Kidney Disease Patients Through Hemodialysis - Faridah, Virgianti Nur (Bali Medika Jurnal, 2020)
Patients with CKD disease that has reached grade 5 or the final stage will experience disturbances, not only limited to the kidney system, but other bodies can also be affected which can cause a decrease in health status and sleep quality. The purpose of this study was to examine with literature review the effect of progressive muscle relaxation techniques on the sleep quality of patients with chronic kidney disease. Regular Review using 4 databases (Scopus, Science Direct, Google Scholar, and PubMed) to search for articles with criteria for articles published in 2015-2020, full text, articles that fit the topic, there are ISSNs, volumes, and number numbers, are numbers progressive muscular relaxation interventions in patients with chronic renal failure. After collecting data, all data were selected according to the inclusion and exclusion criteria, then the study was selected using the PRISMA 2009 flow diagram. Based on the selected 10 article results, progressive muscle relaxation therapy results can improve the sleep quality of chronic renal failure patients. Based on 10 selected articles according to inclusion criteria, Progressive muscle relaxation therapy can applied on kidney failure patients to increase the sleep quality patients.